0057 Changes in Morning Salivary Melatonin Correlate with Prefrontal Responses During Working Memory Performance. (27th April 2018) - Alkozei, A; Kent, H; Knight, S; Killgore, W D
Abstract: Introduction: Humans demonstrate a circadian rhythm of melatonin production that closely tracks the daily light/dark cycle. Profound increases in circulating levels of melatonin are observed during the nighttime but these drop to nearly non-existent levels during daylight hours. While melatonin is known to play a role in preparing the brain and body for sleep, its effects on cognition and brain function are not well understood. We hypothesized that declines in morning salivary melatonin would be associated with increased functional activation within cortical regions involved in alertness, attention, and behavioral control. Methods: We measured the change in salivary melatonin from mid- to late-morning in 26 healthy young adults (12 male; 13 female) who were also exposed to a 30-minute period of blue or amber light followed by functional magnetic resonance imaging (fMRI) at 3T during a working memory task (N-Back). Brain activation during the N-Back task was regressed on change in melatonin scores and the role of light exposure was also assessed. Results: Although overall melatonin levels did not change significantly over the morning at the group level, individual declines in salivary melatonin from 0945 to 1245 were associated with significant increases in activation within the left dorsomedial and right inferior lateral prefrontal cortex ( p < .05, cluster corrected) during the N-Back working memory task. Medial prefrontal activation also correlated modestly with better vigilance performance during the 0-Back ( p < .05), but not the 1-Back or 2-Back conditions. Light condition did not affect the outcomes. Conclusion: Changes in morning salivary melatonin were associated with functional brain responses during a working memory task. The magnitude of decline in salivary melatonin during the late morning hours was associated with increased brain activation within dorsomedial and lateral prefrontal cortex, brain regions involved in vigilance, action selection, and cognitive control. We interpret these associations as reflecting individual differences in circadian phase of melatonin and their potential impact on the morning establishment of prefrontal functioning in the hours following awakening. Support (If Any): USAMRMC (W81XWH-11-1-0056)